“Doctor, do I need any other topical medications for my skin?” - Shalihin, Mohd Shaiful Ehsan (Malaysian Medical Gazette, 2016)
The question above is one of the most frequently asked by patients and their loved ones when their skin condition does not heal completely within the duration hoped for. It is most often asked by those with chronic skin conditions, such as eczema, during a consultation at a skin specialist (dermatologist) clinic or government health clinic. These complaints and worries stem from a lack of understanding of the skin condition that they have. It bears reminding that skin diseases come and go. Usually they cannot be cured completely within the patient’s expected time frame. This is because the root cause of the disease is the relationship between internal and external factors; not a simple reason like a bacterial infection that can be cured with antibiotics.